Pemanfaatan Aplikasi Gamifikasi Wordwall Di Era Pandemi Covid-19 Untuk Meningkatkan Proses Pembelajaran Daring - Syahrizal Dwi Putra; Diah Aryani; Hani Dewi Ariessanti (Sekolah Tinggi Teknik - PLN, 2021)
Gamification applications for online learning are something that needs to be socialized at this time, especially during the pandemic to improve the learning process. SDIT Insan Rabbani / Integrated Islamic School (SIT) Insan Rabbani is an Islamic educational institution that is oriented towards character building for its students. To improve the online learning process in this pandemic era, the school wants to use the concept of gamification in the online learning process. Besides that, teachers also want ways to build school learning content that can increase student engagement for online learning, especially during the current pandemic. So the abdimas team provided a solution by offering counseling on the use of gamification using a wordwall. Wordwall was chosen so that teachers can easily understand the concept of gamification and create various quiz/evaluation templates that are owned by wordwall. The expected target is for teachers to understand concepts and use gamification to increase student involvement in the online learning process.